Estimation of Inelastic Interstorey Drift for OSB/Gypsum Sheathed Cold-Formed Steel Structures under Collapse Level Earthquakes - Xiangbin Liu; Hanheng Wu; Liurui Sang; Lu Sui; Congcong Xu (Advances in Materials Science and Engineering)
In order to estimate the inelastic interstorey drift of cold-formed steel (CFS) framed structures under collapse level earthquakes, the deflection amplification factor ηp is employed in this paper to compute the maximum interstorey drift ratio (IDRmax) from an elastic analysis. For this purpose, a series of CFS wall specimens were tested under cyclic horizontal loads, and then the hysteresis model of the walls was put forward by test results. In terms of the hysteresis model, a large quantity of elastic-plastic time-history analysis of CFS building structures was conducted based on the storey shear-type model. Furthermore, the deflection amplification factor ηp for estimating IDRmax and the parameters were analyzed. The results indicate that the deflection amplification factor ηp is highly dependent on yielding coefficient of storey shear force ξy, storey number N, period of structure T, and ground acceleration records GA. Eventually, an approximate ξy-N-ηp relationship for estimating the deflection amplification factor ηp is proposed in this paper, which can be used for seismic design in practices.